Inside Front Cover. Issue 3 (7th September 2020) - Unknown
Abstract : Abstract : In article number EOM2‐2020‐0029, Zhong‐Shuai Wu and co‐workers summarize the state‐of‐the‐art advances of zinc based micro‐electrochemical energy storage devices in micro‐batteries and micro‐supercapacitors, and highlights merits of cost effectiveness and high performance for miniaturized smart integrated systems. (DOI: 10.1002/eom2.12042 )